Analysis of interdigital spaces during mouse limb development at intervals following amniotic sac puncture - CHANG, H.-H. (1998)
A spectrum of limb abnormalities ranging from adactyly, syndactyly, acrosyndactyly to nail hypoplasia was encountered in mouse embryos subjected to amniotic sac puncture at the corresponding gestational stage when human chorionic villus sampling (cvs) would normally be performed clinically. Previous skeletal studies revealed that, apart from the occasional incidence of fusion of 2 distal phalanges, syndactyly usually only affected the soft tissues within the interdigital spaces. A similar situation was also observed in cases of adactyly; while the skeletal elements of the digits were present, the soft tissues in the interdigital spaces failed to separate. A transient period of bradycardia is induced, possibly secondary to compression of the embryo by the extraembryonic membranes and uterine muscles following amniotic sac puncture. These factors, we believe, produce temporary hypoxia/ischaemia of the distal extremities, and may lead to the modification of the interdigital mesenchymal tissues within the autopods. In order to investigate the mechanism(s) underlying soft tissue syndactyly, limbs recovered at 0.5, 4, 8, 12, 24, or 36 h following amniotic sac puncture (ASP) were examined histologically. Vascular disruption in the form of localised areas of haemorrhage, vascular dilatation and congestion and the presence of fluid-filled cavities occurred in relation to the marginal vein and vascular plexus in the interdigital spaces. It is hypothesised that this interfered with the normal equilibrium of the preset programs of mitosis/cell death and apoptosis within the mesenchymal cells of the interdigital spaces. Apoptosis in these areas was inhibited in the majority of the experimental limbs analysed 4 h after ASP. Instead of undergoing necrosis/apoptosis, increased mitotic activity was usually observed from 8 h following ASP at the sites where apoptosis would normally be expected to be seen. The aberrant fate of the interdigital mesenchyme following ASP and the underlying mechanism(s) involved are discussed, as is the critical importance of an adequate vascular supply to the interdigital spaces during the morphogenesis of the autopod. We believe that this report contributes to understanding the mechanism(s) which lead to syndactyly following ASP, and the limb defects occasionally seen following cvs when this is undertaken during early gestation.